1991
DOI: 10.1021/bi00239a024
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle x-ray scattering study of calmodulin bound to two peptides corresponding to parts of the calmodulin-binding domain of the plasma membrane calcium pump

Abstract: The interaction between calmodulin (CaM) and two synthetic peptides, C20W and C24W, corresponding to parts of the calmodulin-binding domain of the Ca2+ pump of human erythrocytes, has been studied by using small-angle X-ray scattering (SAXS). The total length of the CaM-binding domain of the enzyme is estimated to be 28 amino acids. C20W contains the 20 N-terminal amino acids of this domain, C24W the 24 C-terminal amino acids. The experiments have shown that the binding of either peptide results in a complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
77
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 28 publications
11
77
0
Order By: Relevance
“…Small angle x-ray scattering experiments with calmodulin and the C20 peptide revealed that only the C-terminal domain of calmodulin bound, and calmodulin remained in an extended, noncollapsed conformation (8). This extended structure was also confirmed by an NMR solution structure of the C20-Ca 2ϩ -calmodulin complex (9).…”
mentioning
confidence: 75%
“…Small angle x-ray scattering experiments with calmodulin and the C20 peptide revealed that only the C-terminal domain of calmodulin bound, and calmodulin remained in an extended, noncollapsed conformation (8). This extended structure was also confirmed by an NMR solution structure of the C20-Ca 2ϩ -calmodulin complex (9).…”
mentioning
confidence: 75%
“…Conserved amino acid residues of CaMBD1 and other CaMBDs were aligned with these important positions. The other CaMBDs were ACA2p (Harper et al, 1998), BCA1p (Malmstrom et al, 1997), plasma membrane Ca 2ϩ pump (PMCA; Kataoka et al, 1991), calcineurin (Kincaid et al, 1988), and calmodulin (CaM) kinase II (Meader et al, 1993). (B) Amino acid residues 21 to 38 of SCA1p, plotted as an ␣-helical wheel.…”
Section: Discussionmentioning
confidence: 99%
“…Structural information has been derived from examination of calmodulin bound to peptides (Ikura et al, 1992;Meador et al, 1992Meador et al, , 1993 and by analysis of structural modifications of calmodulin on its activation of target enzymes (Craig et al, 1987;Persechini et al, 1989;Weber et al, 1989;Kosk-Kosicka and Bzdega, 1991 ;Cao et al, 1993 light-chain kinase (Ikura et al, 1992;Meador et al, 1992) and Ca*'/calmodulin-dependent protein kinase I1 (Meador et al, 1993). The crystal structure of calmodulin bound to Ca2'-ATPase is not known, but the complex appears to adopt a more extended conformation than the globular shape seen with the other peptides (Kataoka et al, 1991). In this work we used an indirect approach to examine the role of specific sequences of calmodulin in target interactions.…”
Section: Discussionmentioning
confidence: 99%